Neuropeptide Y reduces expression of social fear via simultaneous activation of Y1 and Y2 receptors - Kornhuber, Johannes; Zoicas, Iulia (Journal of Psychopharmacology, 2019)
Background: Neuropeptide Y (NPY) has anxiolytic effects and facilitates extinction of cued and contextual fear in rodents, thereby acting as a resilience factor against exaggerated fear responses after adverse events. We investigated whether NPY influences acquisition, expression and extinction of social fear in a mouse model of social fear conditioning (SFC). Methods: NPY was administered intracerebroventricularly before SFC or before social fear extinction with or without prior administration of Y1 and/or Y2 receptor antagonists. Results: We show that NPY affects SFC-induced social fear in a time point-dependent manner. When administered before SFC, NPY did not affect acquisition, expression and extinction of social fear. However, when administered before social fear extinction, NPY reduced expression of social fear via simultaneous activation of Y1 and Y2 receptors. As such, neither the Y1 receptor antagonist BIBO3304 trifluoroacetate nor the Y2 receptor antagonist BIIE0246 was able to block the effects of NPY completely. However, when administered in combination, they completely blocked the effects of NPY on social fear expression. Conclusions: These findings have important clinical implications, as they suggest that although medication strategies aimed at increasing brain NPY activity are unlikely to prevent the formation of aversive memories after a traumatic social experience, they might improve the recovery from a traumatic social experience by reducing the expression of social fear.
CRIS-Team WoS Importer:2019-08-09